Safety and efficacy of intraoperative Mitomycin C in pterygium - Ali, Araf; Ashraf, Ourfa; Sajjad, Sheikh (International Journal of Research in Medical Sciences, 2022)
Background: Pterygium recurrence rate after simple surgical excision is high. Many adjunctive treatments have been used to reduce the recurrence rates of pterygium development. This study was designed to evaluate the results of intraoperative use of Mitomycin C in patients with single recurrence of pterygium. Methods: this was a hospital based prospective study conducted in the department of ophthalmology SKIMS-MCH, Srinagar from January 2021 to December 2021. 30 eyes of 30 patients who had single recurrence of pterygium after excision underwent pterygium excision along-with concurrent use of intraoperative 0.04% Mitomycin C. Postoperative follow up was done for a period of 6 months. Results: A total of 30 eyes of 30 patients were taken (16 males patients and 14 female patients) with 16 right eyes and 14 left eyes. Recurrence was seen in 3 patients, two males and 1 female at 4 weeks, 6 weeks and 8 weeks respectively. The side effects encountered were ocular discomfort, foreign body sensation, chemosis and hyperaemia. Conclusions: Intraoperative use of Mitomycin C in treatment of recurrent pterygium is safe and effective procedure.